Pengimplemantasian Manajemen Mutu Pendidikan di SMA Negeri 2 Plus Panyabungan - Reni Septrisia; Mursyidan Auliya Nasution; Ummu Salamah; Ummu Hanifah; Rahma Atikah; Muhammad Ali Yusuf; Siti Fatimah Rahmila (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
This research aims to describe the implementation of education quality management at SMA Negeri 2 Plus Panyabungan, Mandailing Natal Regency. This research uses a descriptive method with a qualitative approach. The main respondents consisted of the Deputy Principal and several relevant teachers. Data was collected through observation, interviews and documentation, including the use of school social media as an additional source. This research found that quality management planning at SMA Negeri 2 Plus Panyabungan involved all parties in the organization, from leadership to subordinate staff, in formulating the school's vision, mission and goals. Implementation of quality management uses Total Quality Management (TQM) principles, such as focusing on customers (students and parents), continuous improvement, and a data-based approach. The PDCA (Plan-Do-Check-Act) model is also applied as a systematic approach to improving the educational process. The research results show that the implementation of education quality management is very important in facing the challenges of globalization and technological developments. Effective integrated quality management can improve the quality of education, producing graduates who are academically competent and ready to face the dynamics of the world of work. Therefore, this study provides recommendations to policy makers and education observers to improve the quality of education through integrated and sustainable quality management. In evaluating SMA Negeri 2 Plus Panyabungan, it is the principal who carries out the assessment of teachers, namely in accordance with the SKP or assessment performance standards.